城市环境的建构与保护 = Construction and protection of urban environment - 孔丽娟 Kong, Lijuan (2008)
On the different aspects of administration, economic, environmental science and sociology in the article, the author starts with the concept, construction, development and protection of urban environment. The author analyses the environment problems that the city of Chongqing is faced with, introduces the environment policies and administrative modes of Singapore.